The effectiveness and influence of Vocal and Instrumental Improvisation in Music Therapy on children diagnosed with autism. Pilot Study. - Knapik-Szweda, Sara (Journal of Education Culture and Society, 2020)
Autism is a developmental disorder which is difficult to recognize and diagnose. The present study examines the effectiveness of music therapy intervention based on improvisational techniques with the elements of Creative Music Therapy by Paul Nordoff and Clive Robbins and improvisational techniques by Tony Wigram (such as imitating, frameworking, dialogues, holding) on developmentl of children with Autism (two boys diagnosed with autism - case 1. and case 2), especially in verbal and nonverbal communication, disturbance behavior patterns, cognitive and social-emotional areas. The results indicate a positive outcome in two music therapy observing tools: Scale I Child – Therapist Relationship in Coactive Musical Experience Rating Form and Scale II Musical Communicativeness Rating Form. The tables indicate the intensity of interaction between the therapist and the subject during the music therapy process (including communication skills, cognitive skills and behavior patterns). The results of case 1 are indicated in Scale I and Scale II and show a significant effect of improvisational music therapy. The important findings from the analysis of behavior in the sessions were Stability and confidence in interpersonal musical relationship, Activity relationship developing, (scale 1.). The results of the case 2. show small changes in musical behavior when it comes to Stability and confidence in interpersonal musical relationship, but in Activity relationship developing the indicators show a lot of changes between sessions. The results of the research indicate that music therapy intervention has a positive outcome and may be an effective method to increase functioning of children with autism.